Hypothesis: gonadal temperature influences sex-specific imprinting - Prontera, Paolo; Donti, Emilio (Frontiers in Genetics, 2014)
Various explanations have been advanced for the evolution of genomic imprinting, the most popular of these being the parental conflict hypothesis. However, while this theory may explain why there has been selection for imprinting certain genes, it does not explain how the maternal and paternal genomes can be distinguished from each other. Here, we hypothesize that the temperature at which male and female gonads are physiologically exposed could be, at least for some loci, the primary factor leading to the different imprinting between the sexes.